Students Scientific Attitude in Learning Physics using Problem Based Learning Model with Experimental and Project Methods - Sakliressy, Maura Trynovita; Sunarno, Widha; Nurosyid, Fahru (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2021)
This research aims to determine the differences in the scientific attitudes of students who are given physics learning with the PBL model using experimental methods and project methods on static fluid material. The method used in this research is quantitative with a quasi-experimental approach using two independent group designs, namely the experimental group I using the PBL model-experimental method and the practical group II using the PBL model-project method. Subjects in this study were 65 students of class XI SMA YPPK Teruna Bakti obtained using cluster random sampling technique. Data obtained through a scientific attitude questionnaire instrument consisting of 15 items that have been tested for validity and reliability using SPSS 23.0. Then, the prerequisite test (normality and homogeneity) was carried out and continued with hypothesis testing. The t-test result of 0.026 shows a difference in the average scientific attitude between students who are given learning using the PBL model with the experimental method and students who are given learning using the PBL model with the project method even though the average score for both. Not significantly different, namely in the experimental class 74.14 and the project class 70.10.